1982
DOI: 10.3354/meps008053
|View full text |Cite
|
Sign up to set email alerts
|

Damselfish Territoriality: Influence on Diadema Distribution and Implications for Coral Community Structure

Abstract: Experiments were performed in Discovery Bay (Jamaica, W I.) to determine the relationship between behavior of threespot damselfish Eupornacentrus planifrons Cuvier, and distribution of the common shallow-water echinoid Diaderna antillarum Philippi. E planifrons actively excludes Diadema from its algal lawn, causing a distinct alteration in local distribution of Diaderna on the reef. Physical attacks on the urchin were usually sustained for 2 5 min. The damselfish's agonistic behavior occurred only dunng the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 23 publications
1
38
1
Order By: Relevance
“…Sammarco, 1980;Sammarco and Williams, 1982). It is generally accepted that human activities are responsible for high sea urchin densities because of the removal of predators through over-fishing (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sammarco, 1980;Sammarco and Williams, 1982). It is generally accepted that human activities are responsible for high sea urchin densities because of the removal of predators through over-fishing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Sea urchin densities were measured from July to August, while the water turbulence scale is an annual average, which may account for some of the variation in this dependent variable. (2) Although previous studies have suggested some factors that might explain the distribution of D. antillarum, there are other factors that might have equal importance, such as the aggressive behaviour of territorial pomacentrid fishes (Sammarco and Williams, 1982), and the density of other invertebrate species (Casañas et al, 1998). (3) Neither recruits nor juveniles (test diameter <10 mm) were found during the sampling months, and the inclusion of both recruits and juveniles in addition to adults should be considered in future studies since this may increase the adjusted R 2 value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, tissue may regenerate to cover small lesions very quickly (Bak & Steward-van Es, 1980). Sammarco & Williams (1982) found that damselfish increased the numbers of rarer corals such as Favia because this species is more resistant to algae. From his studies of Pacific damselfish, Potts (1977) concluded that the algal mat caused corals to expend energy to keep surfaces clean, and death followed the exhaustion of metabolic reserves during periods of minimum nutrient availability, Fish and other organisms which prey on corals (Robertson, 1970;Ott & Lewis, 1972;Antonius, 1973;Glynn, 1973;Endean, 1976;Brawley & Adey, 1982) may be responsible for the spread of some of the diseases and microparasites.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that herbivorous damselfish territories, by the nature of their high productivity and extensive cover of the reef substratum, must exert a strong influence on this production. Sammarco & Williams (1982) found that over 50 % of the reef flat on Jamaican back reefs was covered with territories of Eupomacentrus planifrons. The 4 species of damselfish examined by us each occupied territories covering a similarly high proportion of the reef flat (approximately 40 % for Stegastes apicalis) and in which the area1 primary productivity was significantly enhanced (2 to 4 times) over that of the surrounding substratum.…”
Section: Discussionmentioning
confidence: 99%